Millennialism two major views : the Premillennial and Amillennial systems of Biblical interpretation analysed and compared - Feinberg, Charles Lee (Winona Lake, IN BMH, 1985)
Includes bibliographical references and index.
Brethren writer. First ed published 1936. Original title : "Premillennialism or Amillennialism".
Keywords: Millennialism